Missions, Education and Conversion in Colonial Africa - Felix Meier zu Selhausen (African Economic History Network (AEHN), 2019)
This chapter traces the origins and long-term development of African mass-education in colonial sub-Saharan Africa. Specifically, it addresses the unique role of Christian missions in prompting a genuine schooling revolution and explores the comparative educational expansion across colonies and between genders. While the initial expansion of missions was motivated by a global competition for new church members, the development of African mass-education essentially depended on local conditions. It highlights the importance of African agency in the process towards mass-education that depended on local demand for formal education and the supply of African teachers who provided the bulk of mission schooling. The chapter also assesses potential pitfalls when those realities are not considered by studies, investigating historical missionary legacies on present-day African education and social mobility.
Keywords: N37; N57; N97; 330; Christian Missionaries; Education; Africa; Gender; Colonialism; Religion; Human Capital; African Agency